2014
DOI: 10.1161/circep.113.000734
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic Treatment Approach to Ventricular Tachycardia in Cardiac Sarcoidosis [RETRACTED]

Abstract: Background— Fatal arrhythmia is commonly observed in cardiac sarcoidosis, but clinical effects of a systematic treatment approach are still uncertain. This study sought to describe both clinical and electrophysiological characteristics and outcomes of systematic treatment approach to ventricular tachycardia (VT) associated with cardiac sarcoidosis. Methods and Results— We enrolled 37 consecutive patients (11 men; age, 56±11 years) with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 19 publications
4
100
1
2
Order By: Relevance
“…2,4,12,23,24 Our findings confirm and extend the results of the previous studies and show that endocardial with adjuvant epicardial mapping and CA when indicated (ie, recurrent VT or persistent inducibility after endo-only ablation) provides good long-term outcomes, with 40% of patients having no VT at 6-year follow-up and infrequent or isolated recurrent episodes in most of the remaining patients ( Figure 5). However, the efficacy of CA in this patient sample certainly seems lower than other patient cohorts with scar-related VT. 15,25,26 In CS, unlike other forms of scar-related VTs, active inflammation plays a role in promoting VT either by triggered activity or abnormal automaticity or by creating functional slow-conduction pathways within inflamed tissue.…”
Section: Discussionsupporting
confidence: 88%
“…2,4,12,23,24 Our findings confirm and extend the results of the previous studies and show that endocardial with adjuvant epicardial mapping and CA when indicated (ie, recurrent VT or persistent inducibility after endo-only ablation) provides good long-term outcomes, with 40% of patients having no VT at 6-year follow-up and infrequent or isolated recurrent episodes in most of the remaining patients ( Figure 5). However, the efficacy of CA in this patient sample certainly seems lower than other patient cohorts with scar-related VT. 15,25,26 In CS, unlike other forms of scar-related VTs, active inflammation plays a role in promoting VT either by triggered activity or abnormal automaticity or by creating functional slow-conduction pathways within inflamed tissue.…”
Section: Discussionsupporting
confidence: 88%
“…As per the guidelines, FDG-PET is necessary to look for myocardial inflammation. Patchy uptake on FDG-PET is suggestive of inflammation and using immunosuppression may be helpful in the treatment of VT [6].…”
Section: Discussionmentioning
confidence: 99%
“…19 Electrical storm (ES) was defined as the occurrence of 3 episodes of VTs including an appropriate ICD therapy, separated by 5 minutes during a 24-hour period.…”
Section: Definition Of Eventsmentioning
confidence: 99%
“…Gallium scintigraphy and PET are now routinely used to detect inflammation of CS. 16,18,19,33,34 Cardiac PET has high sensitivity and specificity. 14,18,35 In this study, almost all of the patients had positive PET examination.…”
Section: Positive Gallium Scintigraphy As a Factor Correlating With Vtsmentioning
confidence: 99%